Impactos macroeconômicos de investimentos na cadeia de petróleo brasileira - Carlos Wagner de Albuquerque Oliveira; Danilo Santa Cruz Coelho; Luiz Dias Bahia; Joaquim Bento de Souza Ferreira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper tries to quantify some macroeconomic consequences of the Brazilian oil sector investments. The main conclusion is the following: these investments incentivize other investments in the supply chain of the oil sector.
Keywords: D58; 330; Mineralölwirtschaft; Investition; Brasilien